The Closed End Fund in the Vietnam Stock Market: An Examination of Market relation, Foreign Speculation, and Investor Sentiment - Nguyen, Thanh Tung (2007)
The Vietnam stock market is a young and small stock market, but it has attracted much attention from the financial public. The Vietnam stock market is also one of the most volatile markets with 2 “bubbles” and 2 recessions within 1 year. Closed end fund is considered as a measure of the sentiment of individual investors (De Long, Shleifer, Summers, and Waldmann (1990)). Closed end fund is one of the shares that we can measure its fundamentals through the Net Asset Value (NAV). The closed end fund is traded at the discount of its NAV, and that discount is the sentiment of the investor with the market condition. However, according to the observations, during the most optimism of the stock market, there is a period that the closed end fund was traded at a premium, but in other optimistic period, even when the index boosted highly, the fund was still traded at a discount. This is not consistent with the findings of De Long and Shleifer (1990) about the relationship between closed end fund price changes and the stock market bubble in 1929. This paper investigates what drives the premia of the closed end fund in the Vietnamese stock market. In particular, the paper suggests some predictors that can influence the movement of the fund’s price. Emerging markets are attractive to foreign investors. Due to the small size of the markets, capital flows of the foreign investors influence very much on the price movement of the stocks, as well as the premia. The premia can be seen as a measure of the sentiment of the foreign investors toward the local market (Bleany and Smith, 2003). In the Vietnamese stock market, the trading volume of the foreign investors normally accounts for 20% to 30% of the total trading volume, and their behaviors have impact on the behavior of the local investors. And this seems to apply to the closed end funds. In the book “Irrational Exuberance”, Shiller (2000) raised the importance of the individuals’ sentiment on the stock price volatility. Vietnam is a new market which has lots of dividual investors. And their trading is influenced by the emotion This paper will show that the investors’ sentiment also play a part in driving the price of the funds as suggested by many literature on the closed end funds in the emerging markets.